Cardiac platypnea–orthodeoxia syndrome induced by a low-volume state. Issue 3 (4th May 2017) - Ghijselinck, Pieter; Van den Saffele, Jan; Hollanders, Geert
Abstract : We present the case of a 85-year-old patient admitted with palpitations and dyspnea. When assuming a recumbent position, we noticed a significant improvement in dyspnea, as well as a rise in arterial oxygen saturation. This is a typical presentation of platypnea-orthodeoxia syndrome (POS). The diagnosis was confirmed by serial analyses of the arterial oxygen saturation in different positions. In our patient, POS was caused by a cardiac right–left shunt through a patent foramen ovale, facilitated by an atrial septal aneurysm, a dilated aortic root and a large Eustachian valve. A low-volume state, caused by diarrhea and worsened by administration of diuretics in the emergency room, triggered the POS to become clinically apparent. We also noticed a rise in arterial oxygen saturation when the patient was in a hypertensive state. This has never been described before and underlines the influence of hemodynamic changes on the right–left shunt that underlies POS.